2018
DOI: 10.21608/scumj.2018.43541
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Lupus Erythematosus and Irritable Bowel Syndrome: Is Blastocystis Hominis the Missing Piece of the Puzzle

Abstract: Background: Irritable bowel syndrome (IBS) is a chronic functional gastrointestinal disease presenting clinically by abdominal pain with alteration of bowel habits. Although IBS has uncertain etiology, chronic gut inflammation due to persistent exposure to an infectious agent including Blastocystis sp. was proposed. Aim: to determine the prevalence of Blastocystis hominis infestation in Systemic lupus erythematosus (SLE) patients and determining the immunomodulatory effect of Blastocystis hominis on SLE pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Few studies have investigated the relationship between ADs and the presence of Blastocystis . These include ADs such as SLE, RA, spondyloarthritis (SpA), IBD, UC, Crohn’s disease (CD), and IBS [ 107 , 108 , 109 , 110 ]. However, the richness and diversity of the gut microbiome in association with Blastocystis and ADs have only been examined in SpA and IBS patients [ 111 ].…”
Section: Blastocystis and The Gut Microbiomementioning
confidence: 99%
“…Few studies have investigated the relationship between ADs and the presence of Blastocystis . These include ADs such as SLE, RA, spondyloarthritis (SpA), IBD, UC, Crohn’s disease (CD), and IBS [ 107 , 108 , 109 , 110 ]. However, the richness and diversity of the gut microbiome in association with Blastocystis and ADs have only been examined in SpA and IBS patients [ 111 ].…”
Section: Blastocystis and The Gut Microbiomementioning
confidence: 99%
“…Despite the fact that most occurrences of SLE are sporadic and lack genetic predisposing factors, this suggests that other environmental or as-of-yet unidentified variables may also be to blame [24]. Keshawy and Alabbassy [25] showed that Blastocystis hominis infestations, mainly subtypes 2 and 3, were found in 41.66% of the studied SLE patients, which is significantly higher than the percentage found in either IBS patients or healthy controls. This suggests a possible link between Blastocystis hominis and the SLE disease process.…”
Section: Introductionmentioning
confidence: 99%